2021
DOI: 10.1021/acs.inorgchem.0c03480
|View full text |Cite|
|
Sign up to set email alerts
|

Complexation of Cyclic Glutarimidedioxime with Cerium: Surrogating for Redox Behavior of Plutonium

Abstract: The complexation of cerium with glutarimidedioxime (H 2 L) was studied by potentiometry, ESI-mass spectrometry, and cyclic voltammetry. Crystallization of [Ce IV (HL) 3 ] + from Ce 3+ starting reactant indicated spontaneous complexation-driven oxidation. In aqueous solution, Ce 3+ ions form three successive complexes, Ce(HL) 2+ , Ce(HL) 2 + , and Ce(HL) 3 (where HL − stands for the singly deprotonated ligand). The interactions of glutarimidedioxime with metal ions are dominantly electrostatic in nature, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Chelation refers to the process in which central metal ions combine with some suitable coordination atoms to form a complex with a ring structure. Ce 3+ chelated many hydroxylcontaining compounds through Ce−O bonds, such as glutathione, 40 amino tri(methylphosphonic acid), 41 glutaryl dioxime, 42 and quercetin. 43 Furthermore, Ce 3+ aggregated glutathione-modified nanoclusters for fluorescence enhancement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Chelation refers to the process in which central metal ions combine with some suitable coordination atoms to form a complex with a ring structure. Ce 3+ chelated many hydroxylcontaining compounds through Ce−O bonds, such as glutathione, 40 amino tri(methylphosphonic acid), 41 glutaryl dioxime, 42 and quercetin. 43 Furthermore, Ce 3+ aggregated glutathione-modified nanoclusters for fluorescence enhancement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1a ) are metal chelating agents that have been actively studied for metal recovery from wastewaters. Recently, H 2 CID I has been explored for removing uranium (U IV and U VI ) 37 39 cerium (Ce IV ) 40 , 41 , plutonium (Pu IV ) 42 , and neptunium (Np V ) 43 from nuclear wastewater. However, thermodynamic and spectroscopic studies revealed H 2 CID I has higher affinity for V(V) 44 , 45 .…”
Section: Introductionmentioning
confidence: 99%